Climate Change Education Toward Achieving SDG 13 Climate Action: Implications for Elementary School Learning - Umi Wahyu Wardatul Lailiah; Nugrahani Nofita Sari; Yogi Kuncoro Adi (Journal of Educational Sciences, 2026)
Climate change is among the greatest challenges of the 21st century, demanding action across sectors including education. However, implementation of Climate Change Education (CCE) at the elementary school level remains limited and has not been systematically examined in relation to SDG 13. This study synthesizes current literature on CCE, maps instructional models and strategies used in elementary schools, and formulates their pedagogical implications for teaching in Indonesia. A Systematic Literature Review (SLR) following PRISMA guidelines analyzed Scopus- and SINTA-indexed articles published between 2021-2026, yielding 25 eligible articles. The data were analyzed using thematic synthesis to identify the main themes in the reviewed literature. The findings show effective CCE requires contextual, participatory approaches, with STEM, knowledge-building, and climate change camp models enhancing students’ understanding and awareness of climate change. CCE also has implications for climate literacy, pro-environmental attitudes, and teacher competence, requiring structured integration into the elementary curriculum based on SDG 13. This study contributes by examining the relationship between the implementation of CCE and SDG 13 in elementary schools-a connection that has rarely been studied- as a basis for the development of a contextual CCE curriculum in Indonesia. Future research should develop experimental studies incorporating psychosocial and digital literacy dimensions.